Eurocentric Beauty Standards: A Corpus-Assisted Discourse Analysis of Pakistani Skincare Blogs - Memona Mujahid; Salma Kalim (Corporum)
Fueled by digital information sources and advancements in dermatology, increasing public concern for beauty and skincare demands a critical examination of healthcare blog content. Following a mixed-method approach, combining Corpus-Assisted Discourse Analysis (CADS) and Sketch Engine as a tool for examining frequency, wordlists, collocations, and concordances, this study analyzes the language and ideologies in ‘beauty and skincare’ blogs from three Pakistani healthcare websites: Instacare, Healthwire, and Oladoc. The study aims to investigate the linguistic strategies used to promote beauty ideals, particularly the emphasis on skin whitening, and to assess their potential impact on societal beauty norms and public health. The analysis, conducted from the lens of corpus linguistics and Fairclough’s three-dimensional model of discourse, reveals that these blogs predominantly emphasize beauty enhancement and skin-whitening products and narratives, promoting unrealistic expectations and Eurocentric stereotypical beauty standards within Pakistani society at the expense of overall skin health. Additionally, the blogs prioritize promoting dermatological products and treatments over holistic skincare approaches, framing skin as a beauty marker rather than a vital organ. Notably, from the three selected blogs, Instacarere commends organic and natural ingredients. This research argues for the growing need to critically evaluate healthcare website content in the digital age and urges providers to prioritize accurate, medically-supported information over commercial beauty ideals. These findings offer valuable insights for linguists, the general public, healthcare professionals, and website owners.